2018
DOI: 10.4103/jnrp.jnrp_243_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of Yoga in Management of Substance-use Disorders: A Narrative Review

Abstract: Substance use disorders are comparable to chronic medical illnesses and have a chronic relapsing course. Despite being significant contributors to morbidity and mortality, limited treatment options exist. The current narrative review was aimed at providing an overview of yoga therapy in substance-use disorders and discuss the relevant methodological issues. Articles published in English language till May 2017 indexed with PubMed, PubMed central, and Google Scholar were searched using search terms “Yoga,” “Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…In recent years, some review studies have been published trying to identify the benefits of physical exercise in participants who met the criteria for alcohol use disorders (AUD) or other substances use disorders [32][33][34][35][36][37][38] at different levels. Some meta-analysis have also been carried out with the same objective, focusing on SUD patients [39] and AUD patients [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some review studies have been published trying to identify the benefits of physical exercise in participants who met the criteria for alcohol use disorders (AUD) or other substances use disorders [32][33][34][35][36][37][38] at different levels. Some meta-analysis have also been carried out with the same objective, focusing on SUD patients [39] and AUD patients [34].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise is the most commonly used type of exercise for drug addicts [34,39]. However, body-mind activities are increasingly used, such as yoga, tai chi, or qigong [33]. Both practices seem to be beneficial for the treatment of drug dependence, but it is unknown which of the two can generate greater benefits, and whether the use of aerobic exercise or body-mind practices may be more appropriate for aspects of mental disorders and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, interventions such as yoga are increasingly being studied in patients with SUDs and are found to be effective for at least some substance-related parameters. [ 91 ] However, they are yet to be studied in patients with comorbid PD.…”
Section: Management Aspects Of Comorbid Pd and Sudsmentioning
confidence: 99%
“…Studies of yoga in correctional facilities have shown yoga can improve mood, perceived stress, and psychological distress and reduce antisocial behavior among people experiencing incarceration ( Bilderbeck et al, 2013 ; Kerekes et al, 2017 ). Previous studies of yoga for managing substance use disorders suggest yoga reduces substance-related cravings and increases self-reported abstinence ( Kuppili et al, 2018 ). When taught in correctional and reentry settings, yoga and meditation may improve stress and reduce post-release substance use ( Auty et al, 2017 ; Wimberly et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%